Engineering of high performance injection moulded ceramic components by Polarised Light Optical Texture Analysis (PLOTA). (26th May 2009) - Gadow, R.; Kern, F.; Wenzelburger, M.; Rauch, J.
In Ceramic Injection Moulding (CIM) the formation of textures is observed. These frozen flow structures are dependent on the rheological properties of the feedstock, geometric factors of the mould and CIM. The effects of these textures on the mechanical properties of the components produced have to be analysed and quantified in order to reach high quality and reliability standards. The analytical methods need to be exact and reliable to control and optimise the manufacturing process. In this work the optical texture analysis is described. The method is show on an example of injection moulded ceramic gear wheel components.